Effect of deletion of 2, 3-butanediol dehydrogenase gene (bdhA) on acetoin production of Bacillus subtilis. Issue 8 (14th September 2017) - Zhang, Junjiao; Zhao, Xiangying; Zhang, Jiaxiang; Zhao, Chen; Liu, Jianjun; Tian, Yanjun; Yang, Liping
ABSTRACT: The present work aims to block 2, 3-butanediol synthesis in acetoin fermentation of Bacillus subtilis . First, we constructed a recombinant strain BS168D by deleting the 2, 3-butanediol dehydrogenase gene bdhA of the B. subtilis168, and there was almost no 2, 3-butanediol production in 20 g/L of glucose media. The acetoin yield of BS168D reached 6.61 g/L, which was about 1.5 times higher than that of the control B. subtilis168 (4.47 g/L). Then, when the glucose concentration was increased to 100 g/L, the acetoin yield reached 24.6 g/L, but 2.4 g/L of 2, 3-butanediol was detected at the end of fermentation. The analysis of 2, 3-butanediol chiral structure indicated that the main 2, 3-butanediol production of BS168D was meso-2, 3-butanediol, and the bdhA gene was only responsible for (2R, 3R)-2, 3-butanediol synthesis. Therefore, we speculated that there may exit another pathway relating to the meso-2, 3-butanediol synthesis in the B. subtilis . In addition, the results of low oxygen condition fermentation showed that deletion of bdhA gene successfully blocked the reversible transformation between acetoin and 2, 3-butanediol and eliminated the effect of dissolved oxygen on the transformation.